Development of inundation maps along East Coast of Peninsular Malaysia due to predicted seaquake from Manila Trench - Afif Fitri Aziz; Nurul Hani Mardi; Marlinda Abdul Malek; Su Yean Teh; Mohd Azwan Wil; Abd Halim Shuja; Ali Najah Ahmed; Pavitra Kumar; Mohsen Sherif; Ahmed Elshafie (Applied Water Science, 2023)
Abstract Coastal zone has high value of socioeconomic activities. The number of developments and activities at the coastal areas of various sectors has increased day by day. Tsunami hazard is classified as one of the most devastating natural disasters that cause destruction along the coastal areas resulted to human fatalities. There are many causes of tsunami, but the most common is due to earthquake in the ocean. Previously recognised as a safe zone from natural disasters of tsunami, Malaysia was confronted by a rude awakening of the 2004 Andaman tsunami, causing a total loss of 68 lives. However, the potential impacts of tsunamis towards Malaysia coastal areas, especially at East Coast of Peninsular Malaysia, have not been explored extensively. This study, therefore, is critical and pertinent. It aims to investigate the potential seismic activities that generate tsunami occurrences affecting East Coast Peninsular Malaysia. This study further simulates Manila Trench earthquake-induced tsunami at various earthquake intensities, namely Mw 7.0, 8.0 and 9.0, by using TUNA model. Results obtained from this study indicated that tsunami wave generated by Manila Trench earthquake at Mw 9.0 resulted to the highest disastrous effects towards East Coast of Peninsular Malaysia. Findings from this study have established that Kelantan will experience the highest inundation depth at 4.0 m in Pasir Puteh with the highest inland inundation distance at 5.5 km in Bachok. Besides that, Terengganu will experience the highest inundation depth at 6.0 m in Kuala Terengganu with the highest inland inundation distance at 6.0 km also in Kuala Terengganu. In Pahang, the highest inundation depth at 4.5 m with the highest inland inundation distance at 3.3 km is anticipated to experience in Pekan, while in Johor, the highest inundation depth at 1.2 m with the highest inland inundation distance at 0.4 km is anticipated to experience in Mersing. On the other hand, Mw 8.0 and 7.0 earthquake was expected to be insignificant upon arriving at the coastal areas. Mitigation measures and evacuation plans can be effectively planned as findings obtained from this study are able to provide vital information on the possibilities of tsunami waves occurrences to overcome massive losses of properties and life.